Multiple Eruptive Dermatofibroma: A Case Report - Yao MX; Wang YT; Zhou NH (Dove Medical Press, 2024)
Man-Xue Yao,* Yu-Ting Wang,* Nai-Hui Zhou Department of Dermatology, the First Affiliated Hospital of Soochow University, Suzhou, Jiangsu Province, 215006, People's Republic of China*These authors contributed equally to this workCorrespondence: Nai-Hui Zhou, Department of Dermatology, the First Affiliated Hospital of Soochow University, Suzhou, Jiangsu Province, 215006, People's Republic of China, Email zhounaihui@163.comBackground: Multiple eruptive dermatofibroma (MEDF) is a rare presentation of dermatofibroma which is frequently associated with underlying diseases such as human immunodeficiency virus infection or systemic lupus erythematosus. It generally presents a characteristic histology with hyperplasia of the epidermis, prominent bundles of collagen and a diffuse proliferation of fibrocytes.Case Summary: We report a case of MEDF in a 30-year-old man who presented with a large number of dark brownish red maculopapules distributed over the trunk and extremities for more than 10 years. According to the pathology, the patient was diagnosed with MEDF. Infections and autoimmune diseases were ruled out. As he had no clinical symptoms, and presented with lesions widely distributed over the body, we gave no special treatment, but suggested a regular examination.Conclusion: Patients with MEDF usually have no pain and pruritus. If human immunodeficiency virus infection and systemic lupus erythematosus and other causes are ruled out, and lesions are widely distributed over the body, regular check-up is recommended without specific treatment.Keywords: multiple eruptive dermatofibroma, histopathology, immune dysfunction, skin neoplasms, case report